A regional computable general equilibrium model for Honduras: Modeling exogenous shocks and policy alternatives - Morley, Samuel; Piñeiro, Valeria (International Food Policy Research Institute, 2013)
In this paper we develop a dynamic regional computable general equilibrium (CGE) model for Honduras that incorporates regional disaggregated sectors for agriculture. We undertook this research to address two pressing policy concerns in Honduras. First, what growth strategy should the country follow, given its severe balance of payments constraint and dependence on remittances and the price of oil? Second, what would be the impact on growth of investments in projects to increase agricultural productivity, given the importance of agriculture to the rural poor and to the Honduran economy?